Alternative Antibacterial Agents from Endophytic Bacteria of Curry Leaves (Murraya koenigii L. Spreng) for Inhibiting Diarrhea-Causing Bacteria - Diannita Harahap; Rauzatul Firda (International Journal of Science, Technology and Applications, 2025)
This study focused on the isolation and characterization of endophytic bacteria from curry leaves (Murraya koenigii L. Spreng), a medicinal plant known for its health-promoting properties. The research aimed to identify bacterial isolates based on their colony morphology, biochemical characteristics, Gram and endospore staining, and to assess their antibacterial activity against Bacillus cereus ATCC 11788 and Shigella sonnei. Leaf segments (1 cm) were surface-sterilized using 2% sodium hypochlorite three times and cultured on Nutrient Agar supplemented with 0.01% nystatin, followed by incubation at 37°C for 24 hours. A total of nine bacterial isolates were obtained, all showing Gram-positive reactions and positive endospore formation, indicating their classification within the Bacillus genus. The antibacterial activity was tested using the Kirby-Bauer disk diffusion method, revealing that the endophytic isolates exhibited weak inhibitory effects against both tested bacterial strains. These findings suggest that while Bacillus endophytes from M. koenigii possess limited antibacterial potential under the tested conditions, they still hold promise for further investigation as potential sources of bioactive compounds with therapeutic applications.